ChemInform Abstract: Bargellini Condensation of Ninhydrin as a Ketone and Substituted Anilines as Nucleophiles. Issue 29 (29th June 2016) - Rashid, Zahra; Ghahremanzadeh, Ramin; Naeimi, Hossein
Abstract: Novel α‐amino acids based on ninhydrin are conveniently synthesized by NaOH‐promoted Bargellini reaction of various substituted anilines as nucleophiles with ninhydrin and chloroform under mild reaction conditions in high to excellent yields and with high purity.